Consistency in NLO analyses of inclusive and semi-inclusive polarized DIS data - Navarro, G.A. (2003)
We perform a detailed study of the consistency between different sets of polarized deep inelastic scattering data and theory, from the standpoint of a next to leading order QCD global analysis, and following the criteria proposed by Collins and Pumplin. In face of recent suggestions that challenge the usual assumption about parent parton spin independence of unpolarized fragmentation functions, we specially focus on polarized semi-inclusive data.